Fashion victims : dress at the court of Louis XVI and Marie-Antoinette - Chrisman-Campbell, Kimberly (Yale University Press, 2015)
"This engrossing book chronicles one of the most exciting, controversial, and extravagant periods in the history of fashion: the reign of Louis XVI and Marie-Antoinette in 18th-century France. Kimberly Chrisman-Campbell offers a carefully researched glimpse into the turbulent era's sophisticated and largely female-dominated fashion industry, which produced courtly finery as well as promoted a thriving secondhand clothing market outside the royal circle. She discusses in depth the exceptionally imaginative and uninhibited styles of the period immediately before the French Revolution, and also explores fashion's surprising influence on the course of the Revolution itself. The absorbing narrative demonstrates fashion's crucial role as a visible and versatile medium for social commentary, and shows the glittering surface of 18th-century high society as well as its seedy underbelly. Fashion Victims presents a compelling anthology of trends, manners, and personalities from the era, accompanied by gorgeous fashion plates, portraits, and photographs of rare surviving garments. Drawing upon documentary evidence, previously unpublished archival sources, and new information about aristocrats, politicians, and celebrities, this book is an unmatched study of French fashion in the late 18th century, providing astonishing insight, a gripping story, and stylish inspiration"--